Long term effects of micro-surgical testicular sperm extraction on androgen status in patients with non obstructive azoospermia - Comhaire Frank; De Sutter Petra; Van der Elst Josiane; Dhont Marc; Dekuyper Peter; Kerckhaert Wim; De Croo Ilse; Everaert Karel; Mahmoud Ahmed; Lumen Nicolaas (BMC Urology, 2006)
Abstract Background The aim of our study was to review the results of microsurgically performed testicular sperm extraction (TESE) and to evaluate its possible long term effects on serum testosterone (T). Methods We operated on 48 men (35 +/- 8 years) with non-obstructive azoospermia (NOA). If no spermatozoa were found following a micro epididymal sperm extraction (Silber et al., 1994) and testicular biopsy, testicular microdissection was performed or multiple microsurgical testicular biopsies were taken. The mean follow-up of the serum T was 2.4 +/- 1.1 years. Results Sperm was retrieved in 17/48 (35%) of the men. The per couple take home baby rate if sperm was retrieved was 4/17 (24%). Serum T decreased significantly at follow-up (p < 0.05) and 5/31 (16%) de novo androgen deficiencies developed Conclusion In patients with non-obstructive azoospermia in whom no spermatozoa were found following a micro epididymal sperm aspiration and a simple testicular biopsy, we were able to retrieve spermatozoa in 35% of the men. The take home baby rate was 24% among couples with spermatozoa present upon TESE. De novo androgen deficiency occurred in 16% of the male patients following TESE indicating that, in men with NOA, long term hormonal follow up is recommended after TESE.